The Influence of Financial Knowledge and Islamic Behavior on Students' Interest in Sharia Investment - Yuni K, Kusnul Ciptanila; Wahyudi, M. Adi Trisna; Musfiroh, Anita; Ali, Mohammad Haidar; Hidayat, Nurul; Dardiri, Masyhudan (Studia Economica : Jurnal Ekonomi Islam, 2024)
This research explores the impact of financial knowledge and Islamic Behavior on students' investment interests in Islamic capital markets. The quantitative research method uses a questionnaire distributed online to students of the class of 2019-2023 at Hashim Ashari University's Faculty of Economics, with up to 80 participants participating. The study revealed that students' investment interest in the Islamic capital market is not significantly influenced by their financial knowledge but rather by the impact of their Islamic Behavior. This was demonstrated through an analysis. At the same time, financial expertise and Islamic Behavior influence students' interest in investing in Islamic capital markets. This finding is essential for understanding what drives business students' interest in investing in Islamic capital markets and how this affects the development of financial education programs and academic Behavior toward Islamic finance. The results of this study are intended to help develop more effective educational and promotional strategies to increase students' interest in investing in Islamic capital markets.